2019
DOI: 10.1128/mbio.00392-19
|View full text |Cite
|
Sign up to set email alerts
|

Nonrandom Distribution of Azole Resistance across the Global Population of Aspergillus fumigatus

Abstract: The emergence of azole resistance in the pathogenic fungus Aspergillus fumigatus has continued to increase, with the dominant resistance mechanisms, consisting of a 34-nucleotide tandem repeat (TR34)/L98H and TR46/Y121F/T289A, now showing a structured global distribution. Using hierarchical clustering and multivariate analysis of 4,049 A. fumigatus isolates collected worldwide and genotyped at nine microsatellite loci using analysis of short tandem repeats of A. fumigatus (STRAf), we show that A. fumigatus can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
107
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(134 citation statements)
references
References 67 publications
14
107
1
Order By: Relevance
“…Azole resistance in A fumigatus due to TR 34 /L98H and more recent TR 46 /Y121F/T289A mutations in cyp 51A has been described from wide geographical areas among both clinical and environmental isolates . This is linked to the widespread use of azole fungicides in agriculture rather than the clinical use of antifungal drugs .…”
Section: Discussionmentioning
confidence: 99%
“…Azole resistance in A fumigatus due to TR 34 /L98H and more recent TR 46 /Y121F/T289A mutations in cyp 51A has been described from wide geographical areas among both clinical and environmental isolates . This is linked to the widespread use of azole fungicides in agriculture rather than the clinical use of antifungal drugs .…”
Section: Discussionmentioning
confidence: 99%
“…Annual surveys in five academic hospitals in the Netherlands showed that azole resistance in A. fumigatus has doubled from 2014 to 2018 [23,24]. Similar data have been reported worldwide [25][26][27][28][29][30][31][32][33][34][35], and an international resistance surveillance group has been set up by ISHAM/ECMM to capture more information on azole resistance worldwide [36,37].…”
Section: Diagnosis Of Aspergillosismentioning
confidence: 76%
“…Aspergillus fumigatus is an opportunistic fungal pathogen with an ecological niche of soil and composting vegetation, where it plays a vital role in ecosystem processes including decomposition and nutrient recycling (Rhodes, 2006;Tekaia & Latgé, 2005;Van De Veerdonk, Gresnigt, Romani, Netea, & Latgé, 2017). The fungus has a vast geographical range, facilitated by the rapid dispersion of airborne conidia that are able to tolerate a broad range of biotic stresses (Pringle et al, 2005;Sewell, Zhu, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, continual exposure to these compounds exerts selective pressures that can facilitate the evolution of azole-resistant A. fumigatus (ARAf). The recent emergence of two ARAf-associated cyp51A alleles, TR 34 /L98H and TR 46 /Y121F/T289A, has raised concern due to their environmental association and increasing prevalence in azole-naive patients (Abdolrasouli et al, 2018;Chowdhary, Kathuria, Xu, & Meis, 2013;Mellado et al, 2007;Sewell, Zhu, et al, 2019;Snelders, Camps, et al, 2012;Stensvold, Jorgensen, & Arendrup, 2012;Van Der Linden et al, 2013;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%